PENGARUH PERUBAHAN KECEPATAN KAPAL TERHADAP TINGGI PERMUKAAN AIR DI SISTEM FLUIDA DI DALAM PALKA PADA KAPAL IKAN MUATAN HIDUP TIPE KATAMARAN DENGAN PENDEKATAN CFD - Sasmito Hadi, Eko; Manik, Parlindungan; Iqbal, M. (Diponegoro University, 2011)
The existence and the use of live fish hold system, can help fishermen to reduce the operating costs in fishpreservation 11.8%. The live fish hold system, which fish hold were given circulation hole so the water insideand outside the hatch is connected, there should be researched about the changes and differences in pressurethat happened when the ship moves.Initial condition where the ship is not moving, surface of water in the fish hold will be the same height with adraught of ship. When the ship began to move out, the pressure of fish hold will decrease along with increasingthe speed of the ship. This will caused a decrease of water surface elevation in fish hold.According the calculation and analysis we found on the speed of 12 knots the water surface elevation in hold ispositive with a value 0,3947 m on to 0,20 m diameter of hole circulation (before variation), 0,4515 m on to 0,15m diameter of hole circulation, 0,4656 m onto 0,25 m diameter of hole circulation, 0,4718 m on to 0,20 mdiameter of two pieces of hole cilculation and -0,9410 m for manual calculation with all variations.The optimum hole circulation was chossen at two pieces of diameter of 0,20 m because on the speed 12 knots,the water elevation is 0,4718 m. This value is the higest among the other variations of the cilculation hole